Students Ability to Read English at Caritas Catholic Senior High School in Tomohon - Tuilan, Jeane; Widodo, Pratowo (International Journal of Psychosocial Rehabilitation, 2020)
The main problem in this study is the weak ability to read English students. There is also the purpose of this research to find out: (1). What is the process of learning English at Caritas Catholic High School in Tomohon? (2). What are the factors of difficulty in the ability to read English students of Catholic Caritas Tomohon Catholic High School? (3). How is the solution implemented by the teacher in overcoming the difficulty factors of English reading ability of Caritas Catholic High School students in Tomohon? The qualitative study method was chosen in this research because the problem to be studied occurred in certain places and situations. The results of this study can be concluded as follows: (1). The process of learning English in Caritas Catholic Senior High School in Tomohon has been going well; this is evidenced by the availability of learning tools owned by the teachers. (2). The most dominant factors of English pronunciation difficulty in Caritas Catholic Senior High School are: Mother Language, Teaching Material, Social Interaction, Learning Media, Family Background, (3). Solutions implemented by English teachers to overcome the difficulty of English pronunciation of students at Caritas Catholic Senior High School by using the classroom language model. This study recommends further research on students' English proficiency.